Correlation of The Total Population of Black Soldier Fly (Hermetia illucens) Larva with The Population of The House Fly (Musca domestica) in Chicken Feces - Azhari Azhari; Evan Kurniawan; Lian Varis Riandi; Winaruddin Winaruddin; M Jalaluddin; Etriwati Etriwati (The International Journal of Tropical Veterinary and Biomedical Research, 2022)
The increase in the house fly population (Musca domestica) indicates pollution from chicken farms due to the chicken feces produced. The house fly population from farms can be reduced by using Black Soldier Fly (BSF) larvae, but the exact number of BSF larvae has yet to be discovered to reduce the house fly population. This study aims to determine the presence of BSF larvae in chicken feces waste media in inhibiting the population of house flies. The research sample used 7-day-old BSF larvae from fishing for BSF flies from nature using organic waste to lay eggs and produce larvae. The research method used a completely randomized design (CRD) consisting of 4 treatments and 3 replications. Treatment without the addition of larvae (P0), 100 grams (P1), 200 grams (P2) and 300 grams (P3) into 1 kg of chicken feces stocked in a 50 cm x 50 cm container. The variable observed was the number of house flies perched on each treatment's feces. The results showed that the number of flies that landed on chicken feces with the addition of 0 g, 100 g, 200 g, and 300 g BSF larvae was 34.33±12.09, 22.33±10.21, 16.33 ±2.08 tails, 11.00±2.64 individuals. Based on the results of statistical analysis, it was found that the population of the house fly was significantly reduced (P0.05) between the addition of 0 grams of BSF larvae, 100 grams, 200 grams and 300 grams. The results of the study concluded that the more BSF larvae added, the less population of house flies perched around chicken feces. The presence of BSF larvae weighing 200 g per kg of chicken feces can reduce the population of flies that perch on chicken feces by 52%.